Credit and blame - Tilly, Charles (Princeton University Press, 2008)
Social scientist Charles Tilly explores the complexities of human relationships, examining what's really going on when we assign credit or cast blame. Everybody does it, but few understand the hidden motivations behind it. With his customary wit and insight, Tilly takes a thought-provoking look at the ways people fault and applaud each other and themselves. The stories he gathers range from the everyday to the altogether unexpected, from the revealingly personal to the insightfully humorous. Drawing examples from literature, history, pop culture, and much more, Tilly argues that people seek not only understanding through credit and blame, but also justice. The punishment must fit the crime, accomplishments should be rewarded, and the guilty parties must always get their just deserts. This book that revolutionizes our understanding of the compliments we pay and the accusations we make.--From publisher description.